Effects of nickel-oxide nanoparticle pre-exposure dispersion status on bioactivity in the mouse lung. Issue 2 (7th February 2016) - Sager, Tina; Wolfarth, Michael; Keane, Michael; Porter, Dale; Castranova, Vincent; Holian, Andrij
Abstract: Nanotechnology is emerging as one of the world's most promising new technologies. From a toxicology perspective, nanoparticles possess two features that promote their bioactivity. The first involves physical–chemical characteristics of the nanoparticle, which include the surface area of the nanoparticle. The second feature is the ability of the nanoparticle to traverse cell membranes. These two important nanoparticle characteristics are greatly influenced by placing nanoparticles in liquid medium prior to animal exposure. Nanoparticles tend to agglomerate and clump in suspension, making it difficult to reproducibly deliver them for in vivo or in vitro experiments, possibly affecting experimental variability. Thus, we hypothesize that nanoparticle dispersion status will correlate with the in vivo bioactivity/toxicity of the particle. To test our hypothesis, nano-sized nickel oxide was suspended in four different dispersion media (phosphate-buffered saline (PBS), dispersion medium (DM), a combination of dipalmitoyl-phosphatidyl choline (DPPC) and albumin in concentrations that mimic diluted alveolar lining fluid), Survanta®, or pluronic (Pluronic F-68). Well-dispersed and poorly dispersed suspensions were generated in each media by varying sonication time on ice utilizing a Branson Sonifer 450 (25W continuous output, 20 min or 5 min, respectively). Mice (male, C57BL/6J, 7-weeks-old) were given 0–80 µg/mouse of nano-sized nickel oxide in the different states of dispersion via pharyngeal aspiration. At 1 and 7 d post-exposure, mice underwent whole lung lavage to assess pulmonary inflammation and injury as a function of dispersion status, dose and time. The results show that pre-exposure dispersion status correlates with pulmonary inflammation and injury. These results indicate that a greater degree of pre-exposure dispersion increases pulmonary inflammation and cytotoxicity, as well as decreases in the integrity of the blood–gas barrier in the lung.